1995
DOI: 10.1901/jaba.1995.28-515
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Establishing Operations for Self‐injury Maintained by Escape

Abstract: Self-injurious behavior (SIB) can be maintained through negative reinforcement when, in the context of training or task requirements, it produces escape as a consequence. Several studies have demonstrated methods for identifying and treating SIB maintained by negative reinforcement; however, few analyses of the establishing operations associated with demand situations have been conducted. The current series of studies illustrates a method for identifying some establishing operations for escape by systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 32 publications
7
127
0
3
Order By: Relevance
“…A number of possible interventions exist to attenuate the aversiveness of the original EO, such as poorly presented demands (Carbone, Morgenstern, ZecchinTirri, & Kolberg, 2007;McGill, 1999). These interventions include delivering reinforcement for task compliance (Lalli et al, 1999); embedding demands in the context of preferred activities (Carr et al, 1980); using errorless learning (Ebanks & Fisher, 2003); fading instructions (Pace, Iwata, Cowdery, Andree, & McIntyre, 1993); altering the duration, rate, and novelty of demands (Smith, Iwata, Goh, & Shore, 1995); varying the tasks (McComas, Hoch, Paone, & El-Roy, 2000); and providing a choice of tasks (Dyer, Dunlap, & Winterling, 1990).…”
Section: Figure 2 Depiction Of the Cmo-s Relation As A Results Of Thmentioning
confidence: 99%
“…A number of possible interventions exist to attenuate the aversiveness of the original EO, such as poorly presented demands (Carbone, Morgenstern, ZecchinTirri, & Kolberg, 2007;McGill, 1999). These interventions include delivering reinforcement for task compliance (Lalli et al, 1999); embedding demands in the context of preferred activities (Carr et al, 1980); using errorless learning (Ebanks & Fisher, 2003); fading instructions (Pace, Iwata, Cowdery, Andree, & McIntyre, 1993); altering the duration, rate, and novelty of demands (Smith, Iwata, Goh, & Shore, 1995); varying the tasks (McComas, Hoch, Paone, & El-Roy, 2000); and providing a choice of tasks (Dyer, Dunlap, & Winterling, 1990).…”
Section: Figure 2 Depiction Of the Cmo-s Relation As A Results Of Thmentioning
confidence: 99%
“…These individuals were exposed to the putative MOs for a longer duration in the MFA and encountered a greater number of instances of the putative reinforcer for their problem behavior. Therefore, it is possible that the relevant MO to evoke problem behavior was absent during the initial SFA sessions, and that the increased exposure to the antecedent variations (e.g., longer duration) may have been sufficient to allow MOs to affect the behavior (Smith, Iwata, Goh, & Shore, 1995). Alternatively, it may have been the case that the longer session duration permitted the participant to more readily contact the reinforcement contingencies.…”
Section: Discussion and Recommendations For Practitionersmentioning
confidence: 99%
“…Investigations of the properties of demands that establish escape motivation are limited. However, investigators have identified a number of dimensions that are salient in one or more cases, including task difficulty (Carr & Durand, 1985a;Weeks & Gaylord-Ross, 1981), type of required motor responses (Dunlap, KernDunlap, Clarke, & Robbins, 1991), number of required responses (Mace, Browder, & Lin, 1987), task novelty (Mace et al, 1987), duration of instructional sessions (Dunlap et al, 1991), rate of task presentation (Smith, Iwata, Goh, & Shore, 1995), unpredictability of events (Flannery & Horner, 1994), and task preference (Dunlap et al, 1991;Foster-Johnson, Ferro, & Dunlap, 1994). In addition, the probability of problem behavior following a particular demand may be reduced by prior or interspersed events such as storytelling (Carr, Newsom, & Binkoff, 1976), social comments (Kennedy, Itkonen, & Lindquist, 1995), demands highly likely to be complied with (Mace & Belfiore, 1990), and advance notification (Tustin, 1995).…”
Section: Social-negative Reinforcementmentioning
confidence: 99%
“…If a behavior is maintained by a particular reinforcement contingency and, with the contingency operative and in the presence of relevant S D s, the behavior sometimes occurs at high rates and sometimes at low rates, the operation of an EO might be suspected. A number of studies have now shown reductions in such variability when EOs are detected and manipulated (Horner, Day, & Day, 1997;Kennedy & Meyer, 1996;O'Reilly, 1995O'Reilly, , 1997Smith et al, 1995).…”
Section: Including the Analysis Of Eos In Functional Analysismentioning
confidence: 99%